2019
DOI: 10.1021/acs.est.9b03878
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Volumetric μXRF and Fluorescence Computed μ-Tomography Reveals Arsenic Three-Dimensional Distribution within IntactPteris vittataFronds

Abstract: The fern Pteris vittata has been the subject of numerous studies because its extreme arsenic hyperaccumulation characteristics. However, information on the arsenic chemical speciation and distribution across cell types within intact frozen-hydrated Pteris vittata fronds is necessary to better understand the arsenic biotransformation pathways in this unusual fern. While 2D X-ray absorption spectroscopy imaging studies show that different chemical forms of arsenic -As(III) and As(V)occur across the plant organs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…This approach also was able to show differential spatial accumulation of Zn and Ni depending on the area of Noccaea tymphaea (a Ni hyperaccumulator) tissues studied, as the metals were localized in different types of leaf cells, but the same areas of the seeds of the plant . XFI was also used to determine the distribution of toxic contaminants within several plants, revealing that As was accumulated around vascular conducts in fern leaves or Pteris vittata , while La an Ce were found in necrotic areas of the leaves of Dicranopteris lineariz . In addition, XFI has been used more recently to study the interaction between plants and engineered nanomaterials. Specially, XFI studies have provided insight into issues caused by NPs present in the environment during plant growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach also was able to show differential spatial accumulation of Zn and Ni depending on the area of Noccaea tymphaea (a Ni hyperaccumulator) tissues studied, as the metals were localized in different types of leaf cells, but the same areas of the seeds of the plant . XFI was also used to determine the distribution of toxic contaminants within several plants, revealing that As was accumulated around vascular conducts in fern leaves or Pteris vittata , while La an Ce were found in necrotic areas of the leaves of Dicranopteris lineariz . In addition, XFI has been used more recently to study the interaction between plants and engineered nanomaterials. Specially, XFI studies have provided insight into issues caused by NPs present in the environment during plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…with different spatial resolution (μm or nm), as well as exogenous environmental elements present as contaminants accumulated by plant species ( i.e ., La, Ce, As, etc . ). , For example, XFI mapping and tomography were used to demonstrate a correlation between Zn and Fe homeostasis, as Zn can be found in the chloroplasts and mitochondria of leaf cells in Fe-deficient plants . This approach also was able to show differential spatial accumulation of Zn and Ni depending on the area of Noccaea tymphaea (a Ni hyperaccumulator) tissues studied, as the metals were localized in different types of leaf cells, but the same areas of the seeds of the plant .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study demonstrated that two closely-related As-accumulating ferns had distinct mechanisms for As uptake, modulating As cycling in As-rich environments. In the second study looking at Pteris vittate , van der Ent et al 72 combined planar and confocal μXRF imaging and fluorescence computed μ-tomography to study the localisation of As in the endodermis and pericycle surrounding the vascular bundles in the rachis and the pinnules of the fern. Arsenic was also accumulated in the vascular bundles connecting into each sporangium, and in some mature sori.…”
Section: Elemental Speciation Analysismentioning
confidence: 99%
“…Phytoextraction is considered as a feasible and cost-efficient in situ remediation strategy for slightly or moderately contaminated environments with heavy metals, including Cu, Mn, As, Cd, and Zn ( Hou et al, 2017 ; Li et al, 2018 ; Ent et al, 2020 ). In fact, phytoextraction has been applied for achieving a substantial removal of arsenic (As) and cadmium (Cd) from environments at large-scale field trials in China ( Li et al, 2018 ; Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%